Does Teacher Burnout and Academic Stress Influence Teacher Effectiveness – A Systematic Review - Gorain, Shishupal; Kalhotra, Satish (Journal of Education Method and Learning Strategy, 2024)
The current study aims to investigate whether teacher burnout and academic stress hinder the effectiveness of secondary school teachers. To identify the research gap, a systematic review of pertinent literature concerning teacher effectiveness and related variables, including demographic factors, was conducted. The following steps were undertaken: Initially, literature was searched across various platforms such as Google, libraries, and books, resulting in the retrieval of 30 survey research papers from diverse journals. Subsequently, these studies were systematically analyzed and discussed, with findings summarized in a table spanning pages 2 and 3. The systematic review adhered to specific steps to survey the related literature. Firstly, during the planning stage, clear "inclusion and exclusion criteria" were established to systematically identify relevant literature. Secondly, in the review stage, a comprehensive "Summary of the Findings" was meticulously analyzed and discussed following the recording of identified studies in a "Systematic Review Table."